Not Just a Pathogen? Description of a Plant-Beneficial Pseudomonas syringae Strain - Passera, Alessandro; Compant, Stéphane; Casati, Paola; Maturo, Maria Giovanna; Battelli, Giovanna; Quaglino, Fabio; Antonielli, Livio; Salerno, Domenico; Brasca, Milena; Toffolatti, Silvia Laura; Mantegazza, Francesco; Delledonne, Massimo; et al. (Frontiers in Microbiology, 2019)
Plants develop in a microbe-rich environment and must interact with a plethora of microorganisms, both pathogenic and beneficial. Indeed, such is the case of Pseudomonas, and its model organisms P. fluorescens and P. syringae, a bacterial genus that has received particular attention because of its beneficial effect on plants and its pathogenic strains. The present study aims to compare plant-beneficial and pathogenic strains belonging to the P. syringae species to get new insights into the distinction between the two types of plant–microbe interactions. In assays carried out under greenhouse conditions, P. syringae pv. syringae strain 260-02 was shown to promote plant-growth and to exert biocontrol of P. syringae pv. tomato strain DC3000, against the Botrytis cinerea fungus and the Cymbidium Ringspot Virus. This P. syringae strain also had a distinct volatile emission profile, as well as a different plant-colonization pattern, visualized by confocal microscopy and gfp labeled strains, compared to strain DC3000. Despite the different behavior, the P. syringae strain 260-02 showed great similarity to pathogenic strains at a genomic level. However, genome analyses highlighted a few differences that form the basis for the following hypotheses regarding strain 260-02. P. syringae strain 260-02: (i) possesses non-functional virulence genes, like the mangotoxin-producing operon Mbo; (ii) has different regulation pathways, suggested by the difference in the autoinducer system and the lack of a virulence activator gene; (iii) has genes encoding DNA methylases different from those found in other P. syringae strains, suggested by the presence of horizontal-gene-transfer-obtained methylases that could affect gene expression.